KONTRIBUSI KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SURVEY DAN PEMETAAN MAHASISWA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 2188-2191 , Yulia (CIVED, 2018)
Abstract— The aim of study is  to find out how great the contribution of emotional intelligence on student learning outcome this type of research is correlation and population is 82 study survey and mapping, in student Faculty of Engineering State University of Padang students with 64 samples. It taken using Proportional Random Sampling technique. The used is primary and secondary data. Primary data was obtained through distributed questionnaires to students, while secondary data is data obtained from Department Lecturer of Civil Engineering whom teach Course Survey and Mapping semester January - June 2016. The Data analysis techniques were: 1) Descriptive analysis, 2) Normality test and linearity test, and 3) Testing Hypothesis. The results showed the conclution that there is a contribution between emotional intelligence on the learning outcomes survey and mapping students Engineering Studies Program Building Engineering Faculty of Engineering State University of Padang with the number of correlation coefficient of 0,642 and the percentage of contribution to learning outcomes by 41,21 %.    Keywords: Emotional Intelligence, Learning Outcomes